2020
DOI: 10.1038/s41598-020-71235-z
|View full text |Cite
|
Sign up to set email alerts
|

Auditory cognition and perception of action video game players

Abstract: A training method to improve speech hearing in noise has proven elusive, with most methods failing to transfer to untrained tasks. one common approach to identify potentially viable training paradigms is to make use of cross-sectional designs. For instance, the consistent finding that people who chose to avidly engage with action video games as part of their normal life also show enhanced performance on non-game visual tasks has been used as a foundation to test the causal impact of such game play via true exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
2
9
1
Order By: Relevance
“…We also note that the benefits we found match what was suggested by Stewart et al (2020) that using an action-based video-game that targets auditory cues for its task resolution should yield benefits in the auditory domain. These authors identified their lack of effects after training with an action video-game as being due to sensory domain specificity (mainly relying on visuo-spatial cues).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…We also note that the benefits we found match what was suggested by Stewart et al (2020) that using an action-based video-game that targets auditory cues for its task resolution should yield benefits in the auditory domain. These authors identified their lack of effects after training with an action video-game as being due to sensory domain specificity (mainly relying on visuo-spatial cues).…”
Section: Discussionsupporting
confidence: 84%
“…The assessments chosen included basic tests of CAP such as dichotic frequency modulation detection, spectro-temporal modulation (STM) detection and discrimination, gap in noise detection, as well as tests of speech in competition, such as spatial release from masking and digits in noise. We additionally included some tests of cognitive processes such as attention and working memory, as some have argued that a cognitive benefit like that associated to action video-games (see Green & Bavelier, 2003), might underlie improvements in hearing ability associated to AT (see study by Zhang et al, 2017; but also that of Stewart et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, these results clearly confirmed our hypothesis that playing an action audio game with spatial interaction is an effective near-transfer training enhancing audiospatial performance in complex listening situations. On the other hand, the finding that playing a non-action platform video game, which demanded spatial attention to a much lesser degree and in a different sensory modality, was about equally effective as the action audio game, was in apparent contrast to the view that learning processes during game play are modality-specific, without transfer from the visual to the auditory domain [26]. It seems as if successful training of “cocktail-party” listening depended on the enhancement of domain-general cognitive aspects of selective attention, which may have been induced by both games to a similar extent, rather than modality-specific factors of auditory spatial perception.…”
Section: Discussionmentioning
confidence: 99%
“…Also, whether a cross-modal transfer of training exists (that is, auditory improvement by video gaming or vice versa) is still an unresolved issue. Recently, a cross-sectional study by Stewart et al [26] investigated effects of action video gaming on the participants’ performance in auditory cognitive and perceptual tasks, such as attention in listening, speech-in-noise perception, and listening in spatialized noise sentences. However, these authors failed to find any association between action video game play and auditory performance, although positive effects of video game play on a visual task were observed, as known from previous studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation